EFEKTIVITAS PEMBELAJARAN TASAWUF DALAM MENCAPAI KECERDASAN EMOSIONAL DAN SPIRITUAL DI PONDOK PESANTREN FAJAR DUNIA BOGOR - Sari Narulita; Devi Kurniati; Andy Hadiyanto (Mozaic : Islam Nusantara, 2021)
The modern world has been engulfed in a spiritual vacuum. Humans will not enjoy life if they cannot find the meaning of life, and it can only be obtained if humans have spirituality within themselves. As one of the disciplines of science in Islam, Sufism can answer the spiritual problems of modern humans. Islamic boarding schools are Islamic education institutions that still apply Sufism learning clearly in their curriculum. One of the pesantren that has emerged and made Sufism the primary plan or prior knowledge is Pondok Pesantren Fajar Dunia. This study aims to describe and analyze the effectiveness of Sufism learning in achieving emotional and spiritual intelligence at Pondok Pesantren Fajar Dunia. This study uses qualitative methods. The findings in this study indicate that the Sufism learning carried out at the Fajar Dunia Islamic Boarding School runs effectively. It refers to the indicators of achievement of the learning goals of Sufism, the learning management process of Tawasuf, the response of students to Sufism learning, and so the learning outcomes of students.